Pengenalan Produk Digital Banking Sebagai Upaya Meningkatkan Literasi Keuangan Syariah Pada Organisasi Pemuda Muhammadiyah Cabang Watukebo Ambulu Jember: Produk Digital Banking Sebagai Upaya Meningkatkan Literasi Keuangan Syariah - Dimas Herliandis; muhlisin rasuki (Universitas Muhammadiyah Jember, 2023)
As one of the industries engaged in the business and financial sector, banking is certainly required to follow developments in accordance with advances in technology and information. The application of digitalization in the banking industry, especially Islamic Banking, is expected to create speed, convenience, flexibility, and convenience in non-cash transactions in the community. Digital Banking Products Sharia Banking is a modernization of old products equipped with features and innovations of financial products that can be accessed by the public. Of course, with the use of this product, people will be accustomed to non-cash transactions in various business transactions and other economic activities. For this reason, there is a need for synergy from related institutions and community organizations as an effort to educate the public regarding the benefits and advantages of Digital Banking products. In addition, this service also provides education for the community on safe and wise tips in conducting non-cash transactions. It is hoped that with this activity, the public will get new and accurate information in the use of Digital Banking products, and can be careful in non-cash transactions to avoid various financial crimes. more than that, increasing public perception and knowledge of the development of Islamic Financial Literacy can certainly improve well. In addition, this service also provides education for the community on safe and wise tips in conducting non-cash transactions. It is hoped that with this activity, the public will get new and accurate information in the use of Digital Banking products, and can be careful in non-cash transactions to avoid various financial crimes. more than that, increasing public perception and knowledge of the development of Islamic Financial Literacy can certainly improve well. In addition, this service also provides education for the community on safe and wise tips in conducting non-cash transactions. It is hoped that with this activity, the public will get new and accurate information in the use of Digital Banking products, and can be careful in non-cash transactions to avoid various financial crimes. more than that, increasing public perception and knowledge of the development of Islamic Financial Literacy can certainly improve well.